The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/nano10122476
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Application of Nanocellulose in Cementitious Materials

Abstract: The development of the concrete industry is always accompanied by some environmental issues such as global warming and energy consumption. Under this circumstance, the application of nanocellulose in cementitious materials is attracting more and more attention in recent years not only because of its renewability and sustainability but also because of its unique properties. To trace the research progress and provide some guidance for future research, the application of nanocellulose to cementitious materials is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Sonication is considered one of the most widely used methods for CNF dispersion and was also found in the present review, in the studies by Sun et al (2017), Claramunt et al (2019), Barnat-Hunek et al (2019), Nassiri et al (2021) and Ez-zaki et al (2021). Yet, although sonication can be effective in dispersing nanocellulose, Guo et al (2020) reported challenges for this treatment, such as the difficulty of converting the adsorbed nanocellulose on cement particles into free nanocellulose that enables the formation of fiber clusters in cementitious matrices.…”
Section: Cellulose Nanofibers (Cnf)mentioning
confidence: 63%
See 1 more Smart Citation
“…Sonication is considered one of the most widely used methods for CNF dispersion and was also found in the present review, in the studies by Sun et al (2017), Claramunt et al (2019), Barnat-Hunek et al (2019), Nassiri et al (2021) and Ez-zaki et al (2021). Yet, although sonication can be effective in dispersing nanocellulose, Guo et al (2020) reported challenges for this treatment, such as the difficulty of converting the adsorbed nanocellulose on cement particles into free nanocellulose that enables the formation of fiber clusters in cementitious matrices.…”
Section: Cellulose Nanofibers (Cnf)mentioning
confidence: 63%
“…Depending on the extraction method employed, nanocellulose can also be divided into a few groups, such as nanofiber cellulose (CNF) and nanocrystals of cellulose (NCC). NCC are commonly known as nanocrystalline cellulose, nanowhiskers, nanocrystals and the monocrystals, while CNF are much finer as they are extracted from the cellulose microfibers present in the biomass, they are usually cited as cellulose microfibrils, nanofibrils or nanofibrillated cellulose and basically consist of long flexible nanoparticles/nanofibrils with interchanged crystalline and amorphous domains (Abdul Khalil et al, 2012;Guo et al, 2020;Dhali et al, 2021). CNFs have dimensions ranging from 5-50 nm in width and 1-5 μm in length, have 50-70% crystallinity and an extremely high surface area (Goncalves et al, 2021).…”
Section: Cellulose Nanofibers (Cnf)mentioning
confidence: 99%
“…Nanomaterials are structures that have at least one dimension between 1 and 100 nm [ 17 , 18 ]. Such materials have revolutionized many domains, out of which the most intensively researched are related to modern medicine, especially regarding biosensors, diagnostics, targeted drug delivery, and therapeutics [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Having such a broad spectrum of applications, nanomaterials should be synthesized as efficiently as possible in order to gain extensive market reach.…”
Section: Conventional Methods Of Nanomaterials Synthesismentioning
confidence: 99%
“…Single cellulose fibers are known for their unique properties, such as high mechanical strength, which puts them in the same league as Kevlar fibers or steel wire [ 50 , 55 , 56 , 57 ]. Due to cellulose’s linear and quite regular structure and many hydroxyl groups in the molecule, cellulose polymers can form ordered crystalline structures and amorphous regions with disordered structures.…”
Section: Cellulose and Nanocellulosementioning
confidence: 99%